Ethnomathematics approach integrated flipped classroom model: Culturally contextualized meaningful learning and flexibility - Rahmi Ramadhani; Edi Syahputra; Elmanani Simamora (Jurnal Elemen, 2023)
The student-centered learning model has yet to adapt to the environment around students, including cultural contexts and traditions, and is less applicable and less effective for improving students' mathematical abilities. The meaningfulness obtained from mathematics learning based on activity has yet to provide optimal results, and there are still contradictions between learning theories and the application results. Therefore, this study aims to provide recommendations for developing new models and theories to optimize flexible and meaningful learning implementation using qualitative research methods with an integrative literature review approach. The results show that student-centered learning needs attention to personal factors and behaviors. Furthermore, learning with a cultural approach through an ethnomathematics context and flexibility in learning are also needed. The implication of this research is to recommend developing a model that integrates the flipped classroom model and the ethnomathematics approach. Meanwhile, a new theory was also proposed due to the development of the Cognitive-Social-Cultural Constructivist Theory of Learning (CSCCTL). Further studies on developing theories from the ethno-flipped classroom model should be conducted.